2011
DOI: 10.1093/nar/gkr869
|View full text |Cite
|
Sign up to set email alerts
|

The MOF-containing NSL complex associates globally with housekeeping genes, but activates only a defined subset

Abstract: The MOF (males absent on the first)-containing NSL (non-specific lethal) complex binds to a subset of active promoters in Drosophila melanogaster and is thought to contribute to proper gene expression. The determinants that target NSL to specific promoters and the circumstances in which the complex engages in regulating transcription are currently unknown. Here, we show that the NSL complex primarily targets active promoters and in particular housekeeping genes, at which it colocalizes with the chromatin remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 57 publications
(128 reference statements)
11
92
0
Order By: Relevance
“…These authors also showed a physical association between SIR2 and E(Z) in larval extracts and on chromatin (Furuyama et al, 2004). The observation that genes with trithorax binding sites are among those selectively activated by the MOF/NSL complex further suggests that a trx-MOF-Sir2-PcG pathway may be broadly used in development (Feller et al, 2012) such that the sequential actions of H4K16 deacetylation then PcG repression terminate transient developmental gene expression. The biochemical activity of trx required to confer heritability of expression state to target genes remains unclear, but interestingly, early studies using the Fab-7 trx/PcG response element implicated histone H4 acetylation as the epigenetic mark leading to the heritable maintenance of Fab-7 linked reporter genes (Cavalli and Paro, 1999).…”
Section: Discussionmentioning
confidence: 93%
“…These authors also showed a physical association between SIR2 and E(Z) in larval extracts and on chromatin (Furuyama et al, 2004). The observation that genes with trithorax binding sites are among those selectively activated by the MOF/NSL complex further suggests that a trx-MOF-Sir2-PcG pathway may be broadly used in development (Feller et al, 2012) such that the sequential actions of H4K16 deacetylation then PcG repression terminate transient developmental gene expression. The biochemical activity of trx required to confer heritability of expression state to target genes remains unclear, but interestingly, early studies using the Fab-7 trx/PcG response element implicated histone H4 acetylation as the epigenetic mark leading to the heritable maintenance of Fab-7 linked reporter genes (Cavalli and Paro, 1999).…”
Section: Discussionmentioning
confidence: 93%
“…MOF recruitment is particularly important as MOF also participates in the nonspecific lethal (NSL) or MBD-R2 complex in both sexes (Raja et al 2010;Feller et al 2012;Lam et al 2012). The NSL complex is found at 5 ′ ends of most active genes, coincident with MSL complex-independent H4K16 acetylation, and is essential for viability in both sexes.…”
Section: Dosage Compensation In Drosophilamentioning
confidence: 99%
“…In Drosophila, the complex associates with promoters of >4000 genes, and loss of the NSL complex binding severely affects their expression levels (Raja et al 2010). The majority of the NSL complex-bound targets were shown to belong to housekeeping genes, and the NSL complex was shown to be required for efficient recruitment of RNA polymerase II at their target promoters (Feller et al 2012;Lam et al 2012).…”
mentioning
confidence: 99%